2019
DOI: 10.1021/acsami.9b09551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concentrated Salt and Resting Protocol on Solid Electrolyte Interface Formation for Improved Cycle Stability of Anode-Free Lithium Metal Batteries

Abstract: The combined effect of concentrated electrolyte and cycling protocol on the cyclic performance of the anode-free battery (AFB) is evaluated systematically. In situ deposition of Li in the AFB configuration in the presence of a concentrated electrolyte containing fluorine-donating salt and resting the deposit enables the formation of stable and uniform SEI. The SEI intercepts the undesirable side reaction between the deposit and solvent in the electrolyte and reduces electrolyte and Li consumption during cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…Beyene et al introduced a resting and cycling protocol for anode‐free full cells, which when combined with a high‐concentration electrolyte, produced a considerably more robust SEI on the surface of the in situ deposited lithium metal. [ 67 ] They employed a twofold approach, where after cell assembly, the cell was charged and lithium was deposited at a low rate of 0.1 mA cm −2 . After the first charge, the cell was rested for 24 h in order to allow the formation of a robust SEI layer rich in fluorinated species, which originates from the LiFSI electrolyte salt.…”
Section: Strategies For Improving Performance Of Anode‐free Full Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyene et al introduced a resting and cycling protocol for anode‐free full cells, which when combined with a high‐concentration electrolyte, produced a considerably more robust SEI on the surface of the in situ deposited lithium metal. [ 67 ] They employed a twofold approach, where after cell assembly, the cell was charged and lithium was deposited at a low rate of 0.1 mA cm −2 . After the first charge, the cell was rested for 24 h in order to allow the formation of a robust SEI layer rich in fluorinated species, which originates from the LiFSI electrolyte salt.…”
Section: Strategies For Improving Performance Of Anode‐free Full Cellsmentioning
confidence: 99%
“…al., favorable optimization of cycling parameters depends significantly on the electrolyte employed. [ 67 ] Genovese et al reported the effects of a “hot formation” procedure, where the initial two cycles were carried out at an elevated temperatures of 40 °C. [ 69 ] They found that the high‐temperature formation cycles enable the deposited lithium metal to form dense, columnar growths, when compared with formation cycles carried out at 20 °C.…”
Section: Strategies For Improving Performance Of Anode‐free Full Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable efforts have recently been made to control Li plating/stripping on the current collector, including the use of various host materials [8][9][10][11][12] , a coherent lattice 13 , and an increase of temperature or pressure 2, [14][15][16][17][18] . While the efficacy of three dimensional (3D) porous current collectors in reducing the effective current density has been proven, their enlarged electroactive surface area can accompany a larger degree of electrolyte decomposition.…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…To overcome these issues, colossal efforts have been made to achieve uniform deposition of Li metal (He et al, 2019;Assegie et al, 2019;Hou et al, 2017, Hou et al, 2019Nan et al, 2019a, Nan et al, 2019bKamphaus et al, 2019;Beyene et al, 2019;Wang et al, 2019a, Wang et al, 2019b. Among these, various additives have been introduced into the electrolytes to restrain the lithium dendrites by stabilizing the SEI (Zhou et al, 2019;Yang et al, 2017;Yu et al, 2019a, Yu et al, 2019b.…”
Section: Introductionmentioning
confidence: 99%